Mycoplasma pneumoniae-related extra-pulmonary diseases and antimicrobial therapy - Poddighe, Dimitri (Elsevier, 2019)
AbstractThe findings by Yang-TI et al. suggested that macrolide-resistance and/or delayed appropriate antimicrobial treatment may contribute to the development of mycoplasma pneumoniae-related extra-pulmonary diseases in children. Indeed, these conditions can have variable clinical expression and severity and may arise in immunologically predisposed children after recurrent/persistent exposure to mycoplasma pneumonia. Copyright 2019, Taiwan Society of Microbiology. Published by Elsevier Taiwan LLC. This is an open access article under the CC BY-NC-ND license (http://creativecommons.org/licenses/by-nc-nd/4.0/
Keywords: Research Subject Categories::MEDICINE